Operative Versus Nonoperative Management of Distal Iliotibial Band Syndrome-Where Do We Stand? A Systematic Review - Ioanna K. Bolia, M.D., M.S., Ph.D; Preston Gammons, B.S; Donald Jay Scholten, M.D; Alexander E. Weber, M.D; Brian R. Waterman, M.D (Elsevier, 2020)
Purpose: To systematically review the operative versus nonoperative methods for management of iliotibial band syndrome (ITBS) with comparison of the respective clinical outcomes. Methods: By adhering to the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines, 3 databases (Medline, Scopus, Web of Science) searched from inception to October 2019 for randomized clinical trials (RCTs) and observational studies on humans that reported the outcomes following operative or nonoperative management of ITBS. Excluded were case reports, case series with <5 participants, review articles, non-English articles, and non-peer-reviewed articles. The Methodological Index for Non-Randomized Studies (MINORS) criteria for observational studies and the Cochrane Risk of Bias Tool for RCTs were used for quality control. Results: There were 15 eligible studies (9 for operative,6 for nonoperative treatment) examining 179 athletes (mean age 27.3 years, range: 17-53) who received conservative therapy for ITBS and 200 athletes (mean age 30.1 years, range: 14-63) who underwent surgical treatment. Most athletes were runners (65%). The mean follow-up time was significantly longer in studies reporting the outcomes following operative compared with nonoperative ITBS treatment (33.5 vs 2 months, respectively, P < .05). Significant variability in the methods used to assess the clinical outcomes precluded meta-analysis. The most commonly reported (7/9 studies, 77.7%) variable for postoperative evaluation in athletes was the return to sport rate (range: 81%-100%). Significant reduction in pain was consistently (6/6 studies,100%) found among the studies reporting the results of conservative ITBS treatment. The included RCTs were of good (1/5, 20%), fair (2/5, 40%), or poor (2/5, 40%) quality, whereas the average MINORS score was 7.4 (range: 3-13) for observational studies. The level of evidence ranged from Level II (6/15 studies) to IV (9/15 studies). Conclusions: Based on the current literature and at a maximum follow-up time of 6 months, conservative therapy can effectively reduce ITBS symptoms in athletes. Multiple surgical options exist for athletes who do not respond to nonoperative measures, with a reported return to sport rate between 81% and 100%. Level of Evidence: Systematic review of Level II and IV studies